Human Rights of Burn Survivors in Nepal (Sambahak: Human Rights Journal, 2025)
Burn is a preventable public health issue yet it continues to cause significant harm to the population, particularly among the most vulnerable. Burn survivors go through physiological changes such as skin tightening, scarring, skin pigmentation, disfigurements, and amputations in case of limb necrotic burn. Additionally, the survivors face psychological adversities including pain, anxiety, depression, post-traumatic stress disorder, disturbance in bodily ideals, alienation and financial pressure due to prolonged hospitalization. While burn injuries are viewed as a public health issue, this study investigates from a human rights perspective. This paper examines the human rights situation of burn survivors in Nepal through an analysis of the existing legal, health, and social practices. The paper aims to highlight the fundamental rights of burn survivors which includes the right to health, life, dignity, non-discrimination, equality, adequate standards of living, and access to redress and rehabilitation. The findings highlight the need to shift the national response from solely medical treatment towards a rights-based, survivor-centric approach that ensures holistic burn care management. Without such measures, burn survivors remain at the intersection of physical pain, mental trauma, institutional neglect, social exclusion, and denied legal protection.